Simulation of Standalone Hybrid Solar-Battery Fed Water Pumping System - Sumithara, A.; Chitra, S. (Journal of Electronics and Informatics, 2022)
A hybrid battery-based solar (Photovoltaic) water pumping system for agriculture applications has been presented in this research. The battery hybrid power generation is utilized as an energy source to accomplish full-scale continuous water delivery, regardless of climatic conditions. The solar photovoltaic (PV) battery system is used as the primary source, with the battery acting as a backup. With that, when the photovoltaic cluster is insufficient to handle water pumping due to weather conditions or around night time, the battery supplies power. Moreover, it is charged by the solar cluster when the water conveyance isn’t needed. As a result, no external inventory is used to charge the batteries. A bidirectional charging control allows to change the battery’s activity mode by using a buck-boost converter. Artificial neural network is proposed as the controller for switching the pulse of the bidirectional converter. MATLAB/SIMULINK software is used for analysing performance of the proposed system.